THE TREND OF ANNULMENT OF MARRIAGE ON THE TERRITORY OF UZBEKISTAN - Abdumalikova Guli-Ra`no (American Journals, 2023)
This article shows the statistics of rulings in Uzbekistan and their impact on the socio-economic life of minors. A collection of information obtained throughout Uzbekistan, showing the procedure and system of annulment of marriage. 20-year dynamics of children in orphanages, that is, indicators of children who have lost their parents or are psychologically and physiologically unhealthy.